1991
DOI: 10.1002/hfm.4530010104
|View full text |Cite
|
Sign up to set email alerts
|

Human and computer integrated manufacturing: A manufacturing strategy based on organization, people, and technology

Abstract: Much of the human factors research in the area of advanced manufacturing has been concerned with human factors in the design and implementation of manufacturing technology. Recent research has shown that competitive manufacturing needs to be based upon developing a manufacturing strategy which satisfies business needs. Investment in technology by itself does little to improve competitiveness and profitability. The article therefore considers the application of human factors in the development of a manufacturin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Kidd, 1991;Helander, 1994). Below is a review and critique of some of the expectations of the WMW based on the experiences of past projects described in the literature.…”
Section: The Wmwmentioning
confidence: 97%
See 2 more Smart Citations
“…Kidd, 1991;Helander, 1994). Below is a review and critique of some of the expectations of the WMW based on the experiences of past projects described in the literature.…”
Section: The Wmwmentioning
confidence: 97%
“…Research in the manufacturing industry and in academia has repeatedly demonstrated that to improve competitiveness and profitability in manufacturing, one must consider how people interact with technology (e.g., Helander, 1994;Kidd, 1991;Siemieniuch & Sinclair, 1995). One must also consider how organizations will adapt to the new conditions (e.g., Bessant, Levy, Ley, Smith, & Tranfield, 1992).…”
Section: Human Factors Of Wmwmentioning
confidence: 98%
See 1 more Smart Citation
“…These failures have both short term and long term effects, including wasting of valuable resources, lower confidence in leadership or increased resistance to change. Since effectiveness of such systems depends upon abilities of the people to compensate for limitations of technology, the organizational and other human factors issues are critical to the success of technology (Kidd 1991, Kidd and.…”
Section: Introductionmentioning
confidence: 99%
“…Kidd (1991) reports, "One study of manufacturing firms in the United Kingdom has shown that of the firms examined, all of them managed to achieve technical success. In other words, all the companies examined got their technical systems installed and fully operational, with all operating problems resolved.…”
mentioning
confidence: 99%